Dream For Freedom (Perspektif Hukum Islam) - Harizan, Harizan (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Based on the factual circumstances nowadays, many people tried to explore the short way to collect the treasures. Supported by the information Technology development made the spreading of any information and business growth easily. Direct selling, Multi Level Marketing, Online Business and Money Game have its upportunities. Dream for Freedom (D4F) with the Key as a symbol, is one of the money game business which growth successfully between years 2015 – 2016. Thousands of participants or members joined the community (known by the dream team). Spectacularly the founder recruited some of influence person, asked them to promote the business through their statements, pictures and videos. Islam as the belief of most people in Indonesia particularly has the guidance in business through the most principles rules, Al-Qur‟an and Hadith. Therefore the writer tried to explore the Dream for Freedom from Islamic Jurisprudence Perspective.